Factors influencing the performance of agricultural extenders in East Ogan Komering Ulu District - Guslina, Rosa; Sari, Yunita; Permata Sari, Fifian (Enrichment : Journal of Management, 2024)
This research aimed to analyze the factors that influenced the performance of agricultural instructors in East Ogan Komering Ulu Regency. The type of research used in this study was a quantitative descriptive method. The data analysis used in this research was multiple regression analysis. The research results showed that the factors influencing the performance of agricultural instructors in East Ogan Komering Ulu Regency were farmer age, gender, work experience, work distance, and education level. The results of the analysis of the coefficient of determination showed that the factors of farmer age, education, work experience, work distance, and education level were 84.7%, and the remainder was influenced by other factors outside the variables of this research. Simultaneous test results showed that the variables farmer age, education, work experience, work distance, and education level had a very real influence on the performance of agricultural instructors in East OKU Regency. Partial test results for all variables had a significant effect on the performance of agricultural instructors in East OKU Regency